Silvana Pampanini (Anna) sceams as a fish seller holds an octopus in front of her - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1953)
Anna Zaccheo (Silvana Pampanini) is the 23-year-old daughter of a cable-railway worker in a small town near Naples. Her family wants her to marry an older, established man, Don Antonio Percuoco (Umberto Spadaro).
Keywords: Forges Davanzati, Domenico, 1914-; Girotti, Massimo, 1918-2003; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Nazzari, Amedeo, 1907-1979; Pampanini, Silvana; Spadaro, Umberto; Stills (motion pictures); Women -- Italy -- Drama